2018
DOI: 10.1016/j.frl.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

CEO tenure and corporate misconduct: Evidence from US banks

Abstract: We test for a link in between risk taking by US banks and CEO power, which we proxy by a CEO's length of tenure and network size. We find that banks are more likely to take on excessive risks when CEO's have a relatively long tenure and large network. The result is robust controlling for other risk characteristics of banks, governance mechanisms, and bank ownership structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 69 publications
2
19
0
Order By: Relevance
“…Second, we contribute to the debate on governance in banking (see Srivastav and Hagendorff, 2016) by providing evidence suggesting that bank boards do little to dampen risk-taking by banks in the face powerful CEOs. Third, we contribute to the literature on CEO power, which has shown that powerful CEOs can impact financial performance , earnings manageme nt practices (Ali and Zhang 2015), dividend policy (Onali et al, 2017), corporate acquisitio ns (Malmendier and Tate 2008), incentive contract design (Morse et al, 2011), the composition of boards of directors (Combs et al, 2007), and the likelihood of engaging in financial misconduct (Altunbaş et al, 2018); our results suggest that powerful CEOs also encourage greater bank risktaking. Finally, we contribute to the 'monitoring v short-termism' debate on the role of institutio na l investors (see Callen and Fang, 2013) by showing that institutional investors appear to favor greater risk-taking by CEOs.…”
Section: Introductionmentioning
confidence: 65%
“…Second, we contribute to the debate on governance in banking (see Srivastav and Hagendorff, 2016) by providing evidence suggesting that bank boards do little to dampen risk-taking by banks in the face powerful CEOs. Third, we contribute to the literature on CEO power, which has shown that powerful CEOs can impact financial performance , earnings manageme nt practices (Ali and Zhang 2015), dividend policy (Onali et al, 2017), corporate acquisitio ns (Malmendier and Tate 2008), incentive contract design (Morse et al, 2011), the composition of boards of directors (Combs et al, 2007), and the likelihood of engaging in financial misconduct (Altunbaş et al, 2018); our results suggest that powerful CEOs also encourage greater bank risktaking. Finally, we contribute to the 'monitoring v short-termism' debate on the role of institutio na l investors (see Callen and Fang, 2013) by showing that institutional investors appear to favor greater risk-taking by CEOs.…”
Section: Introductionmentioning
confidence: 65%
“…Meanwhile, Pathan and Skully (2010) argue that stricter regulatory environment provides sufficient constraints on bank managers from control of the board selection processes, thus making the performance effect of CEO power over bank board independence non-existent. An important observation from this finding is that, regulatory monitoring serves as effective managerial disciplinary tool (Palvia, 2011) as well as substitute for the performance effect of independent directors on banks board to constrain CEO power to engage in corporate misconduct (Altunbaş et al, 2018;Booth et al, 2002), which Laux (2008) argues that it is beneficial for shareholders wealth maximization. Therefore, the second hypothesis (H2) related to board independence is as follows:…”
Section: Ceo Power and Board Independencementioning
confidence: 95%
“…The burden of the analyst’s forecasts would bring pressure on managers, who are willing to destroy the value of firms to avoid severe punishment ofhe market (Degeorge et al 1999 ). Financial misreporting may be facilitated when the CEO is also the firm’s founder, serves as chairman, or belongs to the founding family members 7 (Agrawal and Chadha 2005 ; Dechow et al 1996 ) because of more reliable connections with other top executives and directors (Altunabas et al 2018 ; Khanna et al 2015 ). The economic literature is rich, with empirical and theoretical studies highlighting the role of reputational loss in deterring financial misreporting and aggressive accounting policy (Giannetti and Wang 2016 ; Karpoff and Lott 1993 ; Murphy et al 2009 ).…”
Section: Related Literaturementioning
confidence: 99%